Development of quadcopter for atmospheric data collection - Wayan Suparta; Trie Handayani (JURNAL INFOTEL, 2022)
This research aims to develop a quadrotor system as unmanned aircraft vehicles (UAVs, or drones) for monitoring atmospheric conditions in a targeted area. The system consists of an APM 2.8 arducopter flight controller, Ublox NEO M8N GPS module with compass, Racerstar 920kV 2-4S Brushless Motor, Flysky Receiver FS-iA6B with FS-i6 Remote Control Transmitter, DJI F450 quadcopter frame kits with tall landing gear skid, and a LiPo Battery 3300 mAh 35C. The system is set up and run through a Mission Planner. As for monitoring atmospheric conditions, the system consists of an Arduino Uno ATmega328P, BME280 sensors, and several modules (DS3231 Real-Time Clock (RTC), micro SD card, and 16×2 LCD). Our vehicle with a total weight of 1 kg can fly into space and maneuver to an altitude of more than 200 meters in an average of 10 minutes. Atmospheric conditions such as air temperature, relative humidity, air pressure, altitude, and precipitable water vapor can be measured and logged properly from drones. By this development, the system can be applied in the future to detect or measure weather extremes, air pollution, or monitoring aerial topography automatically when equipped with gas sensors and cameras, respectively.